A = 9a ( 8a - 7) - (8a - 7)
B= ( 6x + 1) (2x+3) + (2x+3) (5x - 4 )
C = ( 7x - 1 ) (4x-3) - (7x-1) (2x+5)
D = (8x-1) - (2x-7) (8x-1)
E = (4x-3) ² - (4x-3) (5x-7)
F = (9 - 4x) - ( 9- 4x)²

1
A = 9a ( 8a - 7) - (8a - 7) B= ( 6x + 1) (2x+3) + (2x+3) (5x - 4 ) C ne compté pas cette première ligne ^^
il faut factoriser?
Oui

Réponses

2013-11-17T21:34:08+01:00
A = 9a ( 8a - 7) - (8a - 7) 
=(8a - 7)(9a-1)

B= ( 6x + 1) (2x+3) + (2x+3) (5x - 4 ) 
=(2x+3) (6x+1+5x-4)
=(2x+3) (11x-3)

C = ( 7x - 1 ) (4x-3) - (7x-1) (2x+5) 
=(7x-1)(4x-3-2x-5)
=(7x-1)(2x-8)
=2(7x-1)(x-4)

D = (8x-1) - (2x-7) (8x-1) 
=(8x-1)(1-2x+7)
=(8x-1)(8-2x)

E = (4x-3) ² - (4x-3) (5x-7) 
=(4x-3)(4x-3)-(4x-3)(5x-7)
=(4x-3)(4x-3-5x+7)
=(4x-3)(-x+4)

F = (9 - 4x) - ( 9- 4x)²  
=( 9- 4x)-( 9- 4x)( 9- 4x)
=( 9- 4x)(1-9+4x)
=( 9- 4x)(4x-8)
=4( 9- 4x)(x-2)